“Antidotarium ” of Nicholas of Salerno : the history of the pharmacopoeia - F. D. Voronov; I. N. Ruzhinskaya (Фармация и фармакология (Пятигорск), 2017)
The purpose of the article is a textual analysis and identification of practical relevancein the contemporary world of medieval manuscript “Antidotarium” of Nicholas of Salerno – an essential source for the history of pharmacy, containing samples of prescription formulas, leading its history through nine centuries, and tested empirically in countless patients. Materials and methods. To achieve this goal we have analyzed, compared and reviewed existing thematic complexes of literary and historical sources available in medieval medicine, including existing official translations of this manuscript. The result is a detailed analysis and comparison of the original manuscript of the XII th century and the official translations of “Antidotarium” of Nicholas of Salerno in medieval English, Dutch and French. The authors are also discussing the identity of the Nicholas of Salerno and the history of his manuscript, its editing, and the influence that the book has provided on the development and evolution of medicine and pharmacy in Europe as a whole. Conclusion. By defining and showing the history of the “Antidotarium” of Nicholas of Salerno, the authors give an opinion on the high practical significance of this manuscript and the possibility of applying the manuscript formulas in the modern world of evidentiary scientific medicine. The question of the need to translate the medieval source into the Russian language is raised, which will make it possible for the first time in Russian literature to examine in detail the rich medieval prescription of “Antidotarium”, and the need for a further careful and detailed analysis of the translation of the manuscript into the realities of modern evidentiary medicine, rational pharmacotherapy and herbal medicine. Authors have the option of making the translation from medieval French, as one of the closest to the classical Latin languages.